Highlights of high-resolution computed tomography imaging in evaluation of complications and co-morbidities in idiopathic pulmonary fibrosis. (February 2020) - Ricci, Francesca; Pugliese, Luca; Cavallo, Armando Ugo; Forcina, Marco; De Stasio, Vincenzo; Presicce, Matteo; Di Tosto, Federica; Di Donna, Carlo; Spiritigliozzi, Luigi; Rogliani, Paola; Floris, Roberto; Chiocchi, Marcello
Idiopathic pulmonary fibrosis (IPF) represents a condition included in the heterogeneous group of interstitial lung diseases without known causes. The recent ATS/ERS/JRS/ALAT guidelines and the white paper published by the Fleischner Society have well-defined diagnosis and management of idiopathic pulmonary fibrosis. Idiopathic pulmonary fibrosis management is complex because it is also influenced by several co-morbidities and complications. The new frontier in idiopathic pulmonary fibrosis is represented by the effort to understand the complex mechanism of the pathogenesis and progression of disease in order to predict several consequences and co-morbidities. In our review, we tried to distinguish co-morbidities from complications of idiopathic pulmonary fibrosis. In each complication, we have reviewed the existing literature and we have emphasized the complex pathobiological pathway which links the progression of idiopathic pulmonary fibrosis to the development of the complication itself. For every co-morbidity, we tried to identify share common risk factors which explain the coexistence of idiopathic pulmonary fibrosis with its co-morbidities. We then analyzed high-resolution computed tomography (CT) aspects of co-morbidities and complications of idiopathic pulmonary fibrosis that the radiologist should be aware of. In this review, we focused on the role of high-resolution CT imaging in the evaluation of co-morbidities and complications in idiopathic pulmonary fibrosis because their early diagnosis and treatment could change the prognosis in patients with idiopathic pulmonary fibrosis. We have also pointed out that in some cases the final combined quantitative CT tools and conventional visual CT score would allow to get an accurate analysis and quantification of disease progression, co-morbidities, and complications of idiopathic pulmonary fibrosis in order to improve staging systems in idiopathic pulmonary fibrosis.